Handbook of food toxicology - Deshpande, S. S. (Food science and technology (Academic Press), 2002)
This text explores toxin sources, mechanisms, routes of exposure and absorption, and their chemical and biological components to prevent contamination of food products and reduce epidemics of foodborne disease.